Analisis Implementasi Kebijakan Pendidikan Bidang Kualitas Pembelajaran Di Sekolah Menengah Pertama Muhammadiyah 7 Medan - Hasanah, Uswatun; Siahaan, Amiruddin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to explore how education policy is implemented and its impact on improving the quality of learning at SMP Muhammadiyah 7 Medan. The policy implementation is conducted through a mutual agreement between the school, school community, and parents, with the main objective of improving the quality of the learning process and producing excellent graduates. This research uses a descriptive qualitative approach, with data collection methods in the form of observation, interviews, and document review. The results showed that there were policy innovations compared to the previous school year, such as the application of the Deep Learning approach in learning, new provisions for teachers regarding the use of school attributes, and the enforcement of time discipline by changing the entry deadline from 07.30 to 07.10. These policies were designed and implemented based on the results of an agreement between internal and external parties of the school.